The D313Y variant in the GLA gene – no evidence of a pathogenic role in Fabry disease. (17th November 2017) - Hasholt, Lis; Ballegaard, Martin; Bundgaard, Henning; Christiansen, Michael; Law, Ian; Lund, Allan M.; Norremolle, Anne; Krogh Rasmussen, Ase; Ravn, Kirstine; Tumer, Zeynep; Wibrand, Flemming; Feldt-Rasmussen, Ulla
Abstract: Fabry disease is an X- linked inherited lysosomal storage disease caused by mutations in the GLA gene encoding the lysosomal enzyme alpha-galactosidase A (α-Gal A). The possible pathological significance of the D313Y variant in the GLA gene has not been verified and it may be a Fabry variant. Our aim was to elucidate whether the presence of the D313Y variant influenced the α-Gal A activity or resulted in Fabry symptoms or Fabry organ involvement. In two Danish families the presence of the D313Y variant did not result in reduced α-Gal A activity or clinical Fabry manifestations in males, and the presence in Fabry females did not significantly enhance the phenotype of a known causative mutation in the GLA gene (G271S). Our findings indicate that the D313Y variant is not causative to nor enhancing Fabry disease phenotype. The D313Y variant in the GLA gene was not disease causative in 2 Danish families. Investigating male family members were crucial in excluding the Fabry phenotype, and thus very important for proper genetic counceling of all family members, as well as overdiagnosing a devastating genetic disease.